Precision genome editing : unleashing the therapeutic potencial of CRISPR/CAS9 in genetic disease treatment - Dinis, Martim Maria Pedro e (2024)
The principal aim of this study was to investigate the potencial therapeutic applications of CRISPR-Cas9 in the treatment of genetic disorders. In particular, the study examines the present applications of CRISPR-Cas9, delineates the associated challenges, and offers insights into prospective enhancements in gene editing tecnologies. This research employs na extensive literature review, encompassing both review articles and original research papers published between 2019 and 2024, augmented by key foundational works. The selected articles address a range of topics, including gene editing, the therapeutic applications of CRISPR-Cas9, and ethical considerations. The databases searched include PubMed, Google Scholar, Web of Science, ScienceDirect, and IEEE Xplore. The following keywords were used for the search: “CRISPR-Cas9,” “gene editing,” and “genetic diseases.” CRISPR-Cas9 has demonstrated efficacy in the in vitro correction of genetic mutations associated with diseases such as cystic fibrosis and Huntington’s disease. Despite the demonstrated efficacy of delivery systems such as viral vectors, lipid nanoparticles, and adenoviral vectors they still face limitations related to immune responses and targeted tissue delivery. The potencial for off-target effects represents a significant concern, raising importante safety and ethical issues, particularly in the context of clinical and therapeutic applications. The advent of next-generation CRISPR systems, such as base editing and prime editing, offers potencial solutions by minimising double-strand breaks and improving precision. The clinical applications of CRISPR-Cas9 for the treatment of genetics diseses represents a significant breakthrough, yet the technology still faces a number of technical and ethical challenges. As the technology develops, enhancements in delivery methodologies, reductions in off-target consequences, and the establishment of ethical guidelines will be vital for ensuring the secure and effective incorporation of CRISPR-Cas9 into medical therapies.